The Charterhouse of Parma, Volume 2 - Stendhal, 1783-1842; Scott-Moncrieff, C. K. (Charles Kenneth), 1889-1930 (Salt Lake City, UT : Project Gutenberg, 2021)
"The Charterhouse of Parma, Volume 2" by Stendhal is a novel published in 1839. This continuation follows young Italian nobleman Fabrice del Dongo as he navigates the treacherous court of Parma, where his devoted aunt Gina and her lover Count Mosca scheme to advance his ecclesiastical career. When Fabrice kills a man in self-defense and faces execution, political intrigue escalates. The novel explores forbidden passions, diplomatic maneuvering, and the corrupting nature of power in post-Napoleonic Italy. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/The_Charterhouse_of_Parma
Release date is 2021-09-25
Laura Natal Rodrigues
Keywords: Love stories; Political fiction; Parma (Italy) -- Fiction; Italy -- Social life and customs -- 19th century -- Fiction; Young men -- Italy -- Parma -- Fiction